A New Subclass of Multivalent Function Defined by Using Jackson Derivative Operator (Global Journal of Science Frontier Research, 2023)
In this paper authors used Jackson Derivative operator to form a new subclass of multivalent function and derived some results for a function belonging to new subclass of multivalent functions Mainly our emphasis on coefficient estimate of functions belonging to new subclass of multivalent function as well as we have also discussed radii of starlikeness convexity and close to convexity properties of a function Our results reduces to the earlier known results of Silverman 1975 Srivastava 1987 Altintas et al 1995 and Khosravianarb et al 2017 by assuming some particular values of the parameters
Keywords: jackson derivative operator; multivalent functions; coefficient estimate; radii of starlikeness